Probing Phenomenological Experiences Through Electroencephalography Brainwave Signals In Neuroarchitecture Study (International Journal of Built Environment and Sustainability, 2019)
Experiences are a part of our daily lives through our interactions with the environment around us. We live life through the realm of experiences, be it playing or working. As we encounter phenomena frequently, it is deduced that most of it comes from within the built environment, considering how most of our time is spent indoors. Hence, it is imperative that we understand the impact of the built environment on human physiology especially within the context of religious spaces which is largely attributed to phenomenological experiences. Despite the importance of understanding the impact of the built environment on human physiology, phenomenological studies that addresses this relationship are still lacking. This presents a gap which necessitates evidence to be provided in the form of phenomenological studies. Hence, this study attempts to address the gap by utilising evidential data with the utilisation of the portable electroencephalography (EEG) device. In doing so, the brainwave readings from four participants at the Tuanku Mizan Zainal Abidin Mosque were observed. Data from the EEG device in the form of brainwave signals was analysed through the performance metrics detection suite which focused on the possibility of analysing brainwave data through three phases of habitation. The findings detected relaxation performance metrics from the participants whilst being within the mosque prayer area, whereas the phases prior to entering and after leaving the mosque appears to have detected higher excitement and engagement levels. Thus, it could be deduced that the interior prayer area of the mosque appears to have had a positive influence on the participant's physiology. This study could contribute to the novel field of neuroarchitecture in Malaysia, an area of study at the threshold of neuroscience and architecture that could be significant in understanding the relationship between the built environment and human physiology.
Keywords: Architecture; Electroencephalography; Mosque; Neuroarchitecture; Phenomenological experiences